2019
DOI: 10.1177/1934578x19864218
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effect of Trixis angustifolia Aqueous Extract on Triton WR-1339- and High-Fat Diet-Induced Hyperlipidemic Mice

Abstract: The aim of the present study was to evaluate the hypolipidemic effect of Trixis angustifolia aqueous extract (TxAE) on Triton WR-1339- and high-fat diet-induced hyperlipidemic mice. In the Triton model, treatment with TxAE at 100 and 200 mg/kg body weight produced a significant decrease in triglycerides and very low-density lipoprotein levels and a significant increase in high-density lipoprotein (HDL). Similarly, administration of TxAE along with the high-fat diet induced a significant decrease in serum total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The hypolipidemic effects of extracts A, B and D were superior to the administration of 200 mg/kg of R. alaternus methanolic extract in a tyloxapolinduced hyperlipidemia model, which reduced the levels of TGs by 70% and TC by 60% (Tacherfiout et al, 2018). The administration of 100 mg/kg T. angustifolia lowered the concentration of TGs by 44% (Salazar-Gomez et al, 2019). On the other hand, the results of this study were similar to those reported for T. atlanticus aqueous extracts reducing TGs by 96.4% and TC by 82.8% (p<0.01) (Ramchoun et al, As in this study, tyloxapol administration did not affect c-HDL concentration, nor did treatment with an aqueous extract of Ocimum basilicum (Amrani et al, 2006).…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales ...mentioning
confidence: 91%
See 2 more Smart Citations
“…The hypolipidemic effects of extracts A, B and D were superior to the administration of 200 mg/kg of R. alaternus methanolic extract in a tyloxapolinduced hyperlipidemia model, which reduced the levels of TGs by 70% and TC by 60% (Tacherfiout et al, 2018). The administration of 100 mg/kg T. angustifolia lowered the concentration of TGs by 44% (Salazar-Gomez et al, 2019). On the other hand, the results of this study were similar to those reported for T. atlanticus aqueous extracts reducing TGs by 96.4% and TC by 82.8% (p<0.01) (Ramchoun et al, As in this study, tyloxapol administration did not affect c-HDL concentration, nor did treatment with an aqueous extract of Ocimum basilicum (Amrani et al, 2006).…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales ...mentioning
confidence: 91%
“…Treatment strategies for dyslipidemia comprise pharmacological (FDA, 2015) and nonpharmacological methods, namely, medicinal plants (Bye & Linares, 2016;Alonso et al, 2017;Aumeeruddy & Mahomoodally, 2022) that contain bioactive compounds or phytochemicals shown to reduce serum lipid levels, e.g., phenolic compounds, flavonoids, and betalains (Ramchoun et al, 2012;Ma et al, 2015;Tacherfiout et al, 2018;Salazar-Gomez et al, 2019;Yahaghi et al, 2020). Xoconostle fruit (O. joconostle) is a good source of the previously mentioned bioactive compounds (Osorio-Esquivel et al 2011;Morales et al, 2012;Morales et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation